2020
DOI: 10.3390/nu12092589
|View full text |Cite
|
Sign up to set email alerts
|

Cow and Human Milk-Derived Exosomes Ameliorate Colitis in DSS Murine Model

Abstract: The aim of this study was to investigate the therapeutic effect of cow and human milk derived exosomes (MDEs) on colitis. We used gavage administration of fluorescent labeled MDEs to track their localization patterns in vivo and studied their therapeutic effect on colitis in a dextran sulfate sodium (DSS)-induced colitis model. MDEs attenuated the severity of colitis induced by DSS and statistically reduced the histopathological scoring grade and shortening of the colon. Likewise, treatment with MDEs reduced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 34 publications
1
71
0
Order By: Relevance
“…Accordingly, levels of IL-10 were increased while those of IL-17A, IL-22, and IL-23R secreted by Th17 cells were reduced in the colon. In consistence with a recent report 49 , elevated levels of the general inflammation markers IL-1β, TNF-α and IL-6 in both serum and colon tissue of UC mice were effectively diminished by mEVs. At the cellular level, mEVs could suppress the production of proinflammatory cytokines and their downstream mediators including TNF-α, NO and PGE2 ( Figure S4 ).…”
Section: Discussionsupporting
confidence: 85%
“…Accordingly, levels of IL-10 were increased while those of IL-17A, IL-22, and IL-23R secreted by Th17 cells were reduced in the colon. In consistence with a recent report 49 , elevated levels of the general inflammation markers IL-1β, TNF-α and IL-6 in both serum and colon tissue of UC mice were effectively diminished by mEVs. At the cellular level, mEVs could suppress the production of proinflammatory cytokines and their downstream mediators including TNF-α, NO and PGE2 ( Figure S4 ).…”
Section: Discussionsupporting
confidence: 85%
“…Another study reported that porcine milk exosomes effectively protected the intestine epithelial cells against Lipopolysaccharide (LPS) -induced injury by protecting against apoptosis and attenuating cell inflammation via exosomal miR-iR-219, and miR-338 (Xie et al, 2019). Reif et al (2020) reported that gavage administration of exosomes derived from bovine and human milk attenuated colitis induced by dextran sulfate sodium in murine model; in addition, it caused a significant reduction in histopathological score and the shortening of the colon, with decreases in the expression levels of interleukin 6 (IL-6) and tumor necrosis factor-α (TNF-α). Type 1 diabetes is regarded as an autoimmune disorder.…”
Section: Milk-derived Evs and Immune Regulationmentioning
confidence: 99%
“…The studies researched the effects of EVs and exosomes on the gut microbiota [ 201 , 223 , 225 ], on the use of a delivery vehicle [ 111 , 159 , 184 , 208 , 213 , 226 , 227 , 228 , 229 , 230 , 231 ], in the immune response [ 60 , 178 , 185 , 203 , 217 , 232 , 233 , 234 , 235 , 236 , 237 ], in diseases such as cancer, [ 188 , 189 , 209 , 228 , 231 , 236 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 ], and in other aspects of cell biology [ 129 , 162 , 248 , 249 , 250 , 251 , 252 , 253 ]. These studies show that milk-derived EVs can have meaningful biological effects in the model systems used, forming a basis for future research.…”
Section: Biological Effects Of Milk-derived Evsmentioning
confidence: 99%